Pengaruh Kelekatan Dengan Orang Tua Terhadap Motivasi Belajar Anak Melalui Self-Efficacy Siswa di Mts. Al-Ittihadiyah Canggu Badas Kediri - Isroiyah, Dewi (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
In psychology, attachment is a strong emotional bond developed through interaction with children that have special meaning in his life. The study reveals that (1) the correlation between attachment of parents and students' self-efficacy was 33%. The influence of attachment of parents to self-efficacy was 10.9%, whereas 89.1% was influenced by other factors outside the model. (2) The correlation between self-efficacy and students' motivation to learn was 68.2%. The influence of self-efficacy on students' motivation to learn was 46.5%, whereas 53.5% was influenced by other factors outside the model. (3) partial correlation between attachment of parents and the motivation of children to learn was 45.3%. The influence of attachment of parents to motivate children to learn was partially by 20.6%, whereas 79.4% was influenced by other factors outside the model. There is interplay between attachments of parents onÂ children's learning motivation enough. (4) Effect of attachment with parents to motivate children to learn through self-efficacy was 52.4%. This means that there is sufficient influence of attachment with parents to motivate children to learn through self-efficacy of students at MTs. Al-Ittihadiyah Canggu.